Social Media Manager - Khilnani, Jatin (ATLAS SkillTech University, 2024)
MOSCOW ONE is a well-known retail store and business platform that focuses mostly on the Indian ethnic wear. Moscow one is a social platform business that offers real ratings, direct engagement between customers, and the development of emerging talent. In the year 2001 launched the official Moscow one page. Since then, it has served millions of people around the town. Moscow one is also on Instagram, Facebook and other social media platforms.
Project Report on Social Media Manager (2022-24) Under the Guidance of Prof. David Wittenberg
Keywords: Social Media; Social Platform